THEURAPETIC RIDING UNTUK ANAK-ANAK BERMASALAH PEMBELAJARAN - Harri Santoso; Noor Aini Ahmad (Majelis Pendidikan Daerah (MPD) Aceh dan Universitas Syiah Kuala, 2016)
Theurapeutic riding is a physical treatment strategies where the movement of horses used to improve posture, balance and common development of mankind with or without difficulties. North American Riding Association and the American Handicaped Hippotherapy Association defines therapeutic horse riding as the use of movement as a tool by a physical therapist, occupational therapist and speech therapist to deal with disabilities, limited function and the disabled as well as in those with neuro-musculoskeletal dysfunction. Special Education Department Malaysia categorize children with special needs, such as impaired, with visual and learning disabilities that is slow to learn, down syndrome, hyperactivity, dyslexia, autism and cerebal palsy. This paper aims to identify the benefits of therapeutic riding on the development of social skills and emotional skills in children with learning disabilities. This is a qualitative study using in-depth interviews, participant observation and document analysis as tools to get the datas. There were two theurapeutic riding instructors and a physiotherapist at the Riding for the Disabled Association Malaysia - Bukit Kiara - Kuala Lumpur as research participant in this study. The results showed that theurapetic riding is very beneficial to the development of emotional, social and physical in children with learning disabilities